A Phenomenological Exploration of Experiences Related to Learning Styles Among Undergraduate Medical Students in a Barbadian Medical School - Ojeh N; Harewood H; Greaves N; Sobers N; Boyce K; Lashley PM; Adams OP; Paul-Charles J; Majumder MAA (Advances in Medical Education and Practice, 2023)
Nkemcho Ojeh,1 Heather Harewood,1 Natalie Greaves,1 Natasha Sobers,2 Koelle Boyce,3 Paula Michele Lashley,1 O Peter Adams,1 Joanne Paul-Charles,1 Md Anwarul Azim Majumder1 1Faculty of Medical Sciences, The University of the West Indies, Cave Hill Campus, Bridgetown, Barbados; 2George Alleyne Chronic Disease Research Centre, The University of the West Indies, Cave Hill Campus, Bridgetown, Barbados; 3Campus Quality Assurance Office, The University of the West Indies, Cave Hill Campus, Bridgetown, BarbadosCorrespondence: Md Anwarul Azim Majumder; Heather Harewood, Faculty of Medical Sciences, The University of the West Indies, Cave Hill Campus, Bridgetown, Barbados, Tel +1 246 4691 ; +1 246 4703, Fax +1 438 9170, Email azim.majumder@cavehill.uwi.edu; heather.harewood@cavehill.uwi.eduIntroduction: Learning style (LS) frameworks have been implemented by educators to promote participatory learning in order to strengthen learner engagement and to enhance learning outcomes. Self-efficacy has been shown to have an association with learning style and is a predictor of clinical performance and other qualities in medical students. This study examined the perspectives of second and final year medical students in a Caribbean-based medical school, relative to their learning approaches, teaching exposures and preparation for assessments.Methods: An interpretivist qualitative approach was used to analyze data from two focus groups, conducted as part of a sequential mixed-methods study (November 2018-February 2019) with medical students in the second and final year of study. Discussions were audio-recorded, transcribed verbatim, and inductively coded with in-depth thematic analysis assisted by NVivo software.Results: Six Year 2 (Female: Male = 5:1) and seven Year 5 (Female: Male = 5:2) participants, ranging between 18 and 34 years and with a range of LS were recruited into the study. Analysis and data reduction produced three organizing themes: “Dynamics of information delivery and acquisition”, “Pivoting”, and “LS identification, awareness and mutability”, and the global construct “Individual and environmental factors modulate the influence of LS preference in triggering self-efficacy”. In managing information received in class, students used textbooks, YouTube videos, and collaborative learning to augment perceived gaps in lectures and their personal notes. Learning style self-awareness is useful for facilitating self-efficacy throughout medical school, especially at points of transition within the programme of study.Conclusion: LS theory and testing appear to be useful for student and teacher awareness. In practice, honing students’ adaptability to varying learning settings may be more relevant in helping students achieve self-efficacy.Keywords: self-efficacy, VARK questionnaire, focus group discussion, pre-clinical and clinical education, Caribbean